Return to Invested Capital and the Performance of Mergers and Acquisitions - Qian, Jun “QJ”; Zhu, Julie Lei (Management Science, 2018)
We evaluate the efficiency of capital deployment for acquiring firms before mergers and acquisitions (M&As), defined as the return on invested capital net of the cost of capital, and link this measure to firms’ postacquisition performance. Acquirers with higher preacquisition net returns on investment have superior long-run operating and stock performance than do acquirers with lower returns. Acquirers with low net returns on investment also underperform matching nonacquirers. The relationship between preacquisition investment return and postacquisition performance is weakened when chief executive officer turnover occurs after deal completion. These results imply that managerial ability in deploying capital and creating value for shareholders persists through M&As. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2766 . This paper was accepted by Wei Jiang, finance.